Digital Rituals and Cultural Remix: Reinterpreting Tari Piring on YouTube - Farlina, Nina (Indonesian Scientific Publication, 2024)
This study investigates the digital transformation of Tari Piring, a traditional Minangkabau plate dance, as it is reinterpreted in contemporary YouTube performances. The research applies visual semiotic analysis and the frameworks of cultural hybridity and mediatization to examine how traditional symbols and values are preserved, modified, or reimagined in digital formats. Three case studies student and community performances recorded between 2020 and 2024 reveal a consistent pattern of visual innovation: traditional props and movements are retained but recontextualized through EDM remixes, neon costumes, and camera-enhanced choreography. Using thematic coding and interpretive analysis, the study identifies key dynamics in these transformations: preservation of iconic symbols, adaptation to digital visual aesthetics, and repositioning of dance as a public, performative commodity. The findings suggest that digital platforms not only mediate cultural expression but actively reshape it, encouraging younger performers to use Tari Piring as a space for identity negotiation and creative experimentation. While these adaptations offer opportunities for cultural revitalization, they also risk aestheticizing tradition in ways that prioritize spectacle over substance. The research concludes that Tari Piring in the digital era exemplifies a hybrid cultural form both rooted and reinvented underscoring the need for critical engagement with heritage in digital performance landscapes.